(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract; This article analyzes the morphological and anatomical structure of the leaf, its importance and main functions in plant life. The external structure of the leaf (leaf band, plate and base) and internal anatomical layers (epidermis, mesophyll, vascular system) were studied. The article describes the role of the leaf in photosynthesis, gas exchange and water evaporation, as well as its evolutionary significance in the .